Effect of temperature, Thickness and environmental conditions on the thermal properties of pure saturated polyether - Rana Al-Flayih (College of Education for Pure Sciences, 1999)
Abstract The aim of this work is to study the effect of surrounding temperature and environmental condition on thermal conductivity coefficient for pure unsaturated poly -Ester and doped with silica oxid and cellulose for different thickness. In general, the results showed that the thermal conductivity coefficient were in creasing for all samples as the surrounding temperature increases for different environmental conditions for different thickness. It has been noticed that the values of thermal coefficient for unsaturated poly -Ester doped with silica oxid or cellulose are decreased in comparison with pure unsaturated poly-Ester at the same surrounding temperature. The values of thermal conductivity of pure unsaturated poly -Ester at surrounding temperature(20,30,40,50, and 60)˚C were (0.46, 0.49, 0.52, 0.58, 0.67) (w/m.˚C) respectively. The values of thermal coefficient for the two case were (0.39, 0.42, 0.45, 0.49, 0.57), (0.38, 0.40, 0.43, 0.47, 0.56) (w/m.˚C) respectively. It is also noticed the values of thermal conductivity for pure or doped sample decreases as the environmental condition. i.e. when the samples immersed in water or in acidic or basic solution, at different immersion time, at 20 ˚C with 4mm thickness.moreover, it has been found that time for both acidic concentration and immersion time have a high effect on thermal conductivity coefficient.